The right to respect for private life: ukrainian approach and European Court of Human Rights practice - Cherneha, Vitalii; Dobkina, Kateryna; Horban, Yevhen; Hrytsyshyna, Larysa; Zalizko, Oksana (DIXI, 2024)
The right to respect for private life is one of the fundamental values in modern society. That is why it is important to ensure its reliable protection. In European practice, in particular, in the practice of the European Court of Human Rights (echr), clear approaches to understanding the essence and constituent elements of the right to private life have been elaborated. However, in Ukraine, despite the establishment of the right to private (personal) life at the constitutional level, the approach to its ensuring is not perfect. In Ukraine, there is no clear definition of the scope and constituent elements of the right to private life, there are ongoing discussions regarding the very concept of “private life”. To improve the current situation in Ukraine, it is worth taking into account the echr practice, which clearly defines the content and constituent elements of the right to private life. It is also necessary to consider the echr practice when ensuring the right to personal data protection, which is an important element of the right to respect for private life. The personal data protection in Ukraine also needs some improvements based on modern European practice in order to bring it into line with European standards.
Keywords: privacy; private life; personal life; personal data protection